Saint-Cyr : a “useful” school for girls? - Picco, Dominique (Univerzita Pardubice, 2008)
The aim of this paper is to present, very shortly, Saint-Cyr - an exceptional school in France, which was completly different from other convents where the girls of the social elite used to be educated during the seventeenth and eighteenth centuries. I choose to use the utility prism to study Saint-Cyr, as a conceptual tool, but one has to bear in mind that this term wasn’t used by the founders, Louis XIV and Madame de Maintenon. I base my work on the intendant’s report and first I will wonder if Saint-Cyr was a “national school” or a “royal one”. Then I will present the objectives of this institution, and more particularly its utility as an educational institution since, as Astruc said, Saint-Cyr’s goal was to “récompenser les enfants des parents qui ont bien mérité de la patrie” and to form goods mothers in every possible social situation.
Keywords: Saint-Cyr; elitní školy; dívčí školy; Francie; 17.-18. století